Creating a prenatal song for an unborn infant during a music therapy program: A longitudinal and microanalytic case study from before birth to three months of age. Issue 4 (8th August 2022) - Carvalho, Maria Eduarda; Rincón, Raul; Gameiro, Mariana; Rodrigues, Helena
ABSTRACT: Introduction: In music therapy the prenatal songs for unborn infants have been shown to improve prenatal bonding, but we know little about their contribution to the first vocal interactions between mothers and infants up to three months of age. We aimed to explore: (a) the development of maternal singing from gestation until three months of age; (b) fetal and infant responsiveness to a prenatal song and (c) the effect of infant's vocal responsiveness at three months of age for the tonal modulation of maternal singing. Method: A case study of a mother—infant dyad was carried out in a music therapy program where a prenatal song for the unborn infant was created. A video recording of the dyad's interaction was made based on a protocol where the mother hummed an improvised tune and sang the prenatal song to the unborn infant (during a 4D interactive ultrasound) and to the infant at nine days and three months of age. A microanalysis of the fetal movements and the dyad's vocalizations was carried out. Results: We found (a) an episode of fetal motor self-exploration after exposure to the prenatal song, (b) significantly longer infant vocalizations during the prenatal song than during humming (p = 0.01) and silence (p = 0.03) at three months of age, and (c) an increase of pitch in maternal singing following infant vocalizations. Discussion: This study underlined the role of the prenatal singing to promote the interaction between parents and unborn infant and to improve the infant's vocal responsiveness at three months of age.